Protocol of a cross-sectional, multicentre and multidisciplinary study describing phenotype and burden of a midfacial segment pain - Marcin Straburzyński; Adrian M Agius; Magdalena Boczarska-Jedynak; Eliza Brożek-Mądry; Karolina Dżaman; Elżbieta Gradek Kwinta; Anna Gryglas-Dworak; Magdalena Nowaczewska; Anshul Sama; Joanna Smardz; Hoo Kee Tsang; Mieszko Więckiewicz; et al. (Cephalalgia Reports, 2024)
Background: Midfacial segment pain is a term used in the past in the diagnosis of patients mainly from ear, nose and throat clinics. This type of pain cannot be attributed to other primary or secondary facial pain, but is to a large extent similar to tension-type headache with midfacial location. The purpose of this study is to describe midfacial segment pain phenotype, burden and comorbidities in a multicentre and multidisciplinary setting. The ultimate goal is a comprehensive description of this type of pain allowing for its implementation in future classifications. Methods: This cross-sectional study is designed to describe midfacial segment pain in a clinical setting. Patients from rhinologic, headache and facial pain or oral medicine/dentistry secondary care centres will be recruited during a 1 year period. Individuals with other facial pain according to current classification such as sinonasal disorders, neoplasms, local infections, history of significant trauma associated with pain onset will be excluded. Data will be collected through a structured questionnaire covering pain characteristics, coexisting diagnoses, pain-related burden and consequences, physical examination and paranasal sinuses imaging.